2015
DOI: 10.1021/acs.chemmater.5b01860
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Design of Light-Responsive Hydrogels, For in Situ Generation of Fast and Reversible Valves for Microfluidic Applications

Abstract: Light--responsive hydrogel valves with enhanced response characteristics compatible with microfluidics have been obtained by optimization of molecular design of spiropyran photoswitches and gel composition. Self--protonating gel formulations were exploited, wherein acrylic acid was copolymerized in the hydrogel network as an internal proton do--nor, to achieve a swollen state of the hydrogel in water at neutral pH. Light--responsive properties were endowed upon the hydrogels by copolymerization of spiropyran c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
144
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 150 publications
(146 citation statements)
references
References 34 publications
2
144
0
Order By: Relevance
“…Previous work on spiropyran photochromic systems include their use for photo-induced optical sensing of metal ions, continuous flow optical sensing of solvents of different polarity [23,24], reversible photo-actuators for microfluidic applications [25][26][27], photo-chemopropulsion of microdroplets [28], and self-assembly [29,30], among others. More recently it was demonstrated that the conversion between the SP and MC form can be achieved also mechanically under tensile loading, showing the capability to create mechanochromic materials using SP containing polymers [31].…”
Section: Introductionmentioning
confidence: 99%
“…Previous work on spiropyran photochromic systems include their use for photo-induced optical sensing of metal ions, continuous flow optical sensing of solvents of different polarity [23,24], reversible photo-actuators for microfluidic applications [25][26][27], photo-chemopropulsion of microdroplets [28], and self-assembly [29,30], among others. More recently it was demonstrated that the conversion between the SP and MC form can be achieved also mechanically under tensile loading, showing the capability to create mechanochromic materials using SP containing polymers [31].…”
Section: Introductionmentioning
confidence: 99%
“…UV light irradiation (365 nm) causes the azobenzene units to change to the cis state, disrupting the host-guest complexes and expanding the network. [131] Photothermal actuators are particularly inter esting, where actuation with harmless irradiation (e.g., NIR) is required. Gels immersed in water were found to increase up to 124 wt% in weight upon UV irradiation and decrease back to 104 wt% upon visible light irradiation.…”
Section: Soft Actuatorsmentioning
confidence: 99%
“…Many photochromic molecules have been studied, but three of the best-known are spirobenzopyrans (SP) [54-56, 59, 60], azobenzenes [61,62], and diarylethenes [63], all of which show reversible photochromic behaviour, transforming from one isomer to another when exposed to different wavelengths of light. Much research has been carried out into optimising the photo-response of these materials when incorporated into hydrogel matrices, for exploitation in microfluidic systems as valves, pumps, mixers and alternating the topography of surfaces [64][65][66][67]. In addition to the development of the materials themselves (e.g.…”
Section: Photo-induced Actuationmentioning
confidence: 99%
“…Building on this research, Schiphorst J. et al [67] further improved the actuation kinetics by varying the side chain on the spiropyran derivative. The improved formulation was then polymerised in-situ in a microfluidic channel to create a valve structure and exposed to blue light.…”
Section: B)-d) Depending On the Anion Incorporated Inside The Ionogelmentioning
confidence: 99%
See 1 more Smart Citation